Immigrants' chances of being hired at times of skill shortages : results from a factorial survey experiment among German employers - Mergener, Alexandra [Verfasser]; Maier, Tobias [Verfasser] (My University, 2019)
"Within the context of increasing international labour migration, this article analyses immigrants' chances of being hired in a foreign country by identifying key criteria in employers' recruitment decisions. We focus on the German labour market because the prospering economy and demographic change led to an increase in the number of vacant positions, particularly in medium-skilled occupations. The German government, therefore, facilitated labour market access for foreign skilled workers with the intention of minimising shortages on the labour market by means of evaluating the foreign education investments of individuals. However, employers' perception of the labour market integration of foreign skilled workers has barely been examined. In order to directly consider human resources professionals, we use a factorial survey experiment to simulate different hiring scenarios for applicants from Germany and both European and non-European countries. Our design can distinguish between the effects of external circumstances, such as applicant shortages, and applicant-specific characteristics, including nationality, foreign certificates or language skills. The findings reveal that immigrants experience greater chances of being hired in the German labour market in understaffed occupations and in businesses which expect future skill shortages. Language skills and country-specific work experience also substantially improve immigrants' chances of being hired. However, foreign qualifications are viewed more critically during recruitment processes." (Authors' abstract, BIBB-Doku)
OnlineFirst 02 July 2018 (bereits in JB 2018 berücksichtigt)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; G 1.2 Arbeitsmarkt; P 1.5 Migranten; T 3 Forschungsmethoden; Fachkräftemangel; Arbeitsmarktpolitik; Personalgewinnung; Berufliche Integration; Migrant; Rational-Choice-Theorie; Faktorieller Survey